Assessment of the dimensions, construct validity, and utility for rheumatoid arthritis screening of the COPCORD instrument (2014)
This study aims to evaluate the structural validity of the Community-Oriented Program for the Control of Rheumatic Diseases (COPCORD) core instrument as a screening tool for rheumatoid arthritis (RA) by means of assessing the existence of domains in the questionnaire. The Mexican version of the COPCORD instrument was applied to individuals over18 years of age in five regions of the country through a probabilistic/convenience household survey. Clinical confirmation of RA diagnosis was used. T